Circaea mollis Siebold & Zucc. Alleviates postmenopausal osteoporosis in a mouse model via the BMP-2/4/Runx2 pathway - Park, Ji Hye; Son, Yang Ju; Lee, Chang Ho; Nho, Chu Won; Yoo, Gyhye (BMC, 2020)
Background: Circaea mollis Sieb. & Zucc. has been used as a traditional herbal medicine in Hani Ethnopharmacy and possesses anti-arthritic activities. This study aimed to investigate the effect of Circaea mollis Siebold & Zucc on postmenopausal osteoporosis. Methods: For in vitro study, MCF7 breast cancer cells and MC3T3-E1 pre-osteoblast cells were utilized to estimate estrogenic and osteogenic activity. Osteoblastic markers were measured by western blot and real-time PCR. For in vivo study, female mature C57BL/6 mice were ovariectomized and oral administrated with 10 mg/kg and 40 mg/kg of EECM respectively. Results: EtOH extract of Circaea mollis Siebold & Zucc. (EECM) increased alkaline phosphatase activity and osteoblast marker levels at day 7 during differentiation of mouse preosteoblasts. EECM reduced osteoclast differentiation and bone resorption in an osteoblast-osteoclast primary co-culture system. In ovariectomized mice, EECM prevented the decrease in bone mineral density and recovered OSX and Runx2 via BMP2/4, Smad1/5/9 and p38. Conclusions: The results suggest that EECM may be effective in preventing bone loss, offering a promising alternative for the nutritional management of postmenopausal osteoporosis.
Keywords: ESTROGEN-RECEPTOR-ALPHA; DIFFERENTIATION; OSTEOBLAST; EXPRESSION; CELLS; OSTEOCLASTS; PREVENTION; MECHANISMS; INDUCTION